Insulin secretory defect in familial partial lipodystrophy Type 2 and successful long‐term treatment with a glucagon‐like peptide 1 receptor agonist. Issue 12 (15th November 2017) - Banning, F.; Rottenkolber, M.; Freibothe, I.; Seissler, J.; Lechner, A.
Abstract: Background: Familial partial lipodystrophies are rare monogenic disorders that are often associated with diabetes. In such cases, it can be difficult to achieve glycaemic control. Case report: We report a 34‐year old woman with familial partial lipodystrophy type 2 (Dunnigan) and diabetes; her hyperglycaemia persisted despite metformin treatment. A combined intravenous glucose tolerance–euglycaemic clamp test showed severe insulin resistance, as expected, but also showed strongly diminished first‐phase insulin secretion. After the latter finding, we added the glucagon‐like peptide‐1 receptor agonist liraglutide to the patient's treatment regimen, which rapidly normalized plasma glucose levels. HbA1c values <42 mmol/mol (6.0%) have now been maintained for over 4 years. Conclusion: This case suggests that a glucagon‐like peptide‐1 receptor agonist may be a useful component of glucose‐lowering therapy in individuals with familial partial lipodystrophy and diabetes mellitus. What's new?: In a case of familial partial lipodystrophy type 2 (Dunnigan) with diabetes, we found an insulin secretory defect in addition to the expected insulin resistance. The addition of the glucagon‐like peptide 1 (GLP‐1) receptor agonist liraglutide to the patient's treatment regimen rapidly improved glycaemic control and the effect has been sustained for over 4 years. GLP‐1 receptor agonists may be a useful treatment for individuals with familial partial lipodystrophy and diabetes.